SISTEM PENGENDALIAN SUHU DAN PEMANTAUAN KELEMBABAN BIJI KOPI PADA MESIN PENYANGRAI BERBASIS ARDUINO 2560 - Permana, Anggi; Setiono, Iman (Gema Teknologi, 2017)
Anggi Permana, Iman Setiono, in this paper explain that along with the development of modern times. Technological advancements were increasingly found in manufacturing products, everything was done to be easy and practical. These products are made with the aim of helping human work. However, not all manufacturing products are automated. Some products still work manually. Therefore, we are required to be able to innovate by changing the manual process with a more efficient method by using products that are automatic. One tool is the roasting machine for coffee beans. Currently on the market it is rare for automatic coffee roasters to be designed. Most coffee roasters are done manually, use hand mixers, and use wood stoves or gas stoves. This situation becomes less efficient where the roasting is still using the hands, causing it to ripen evenly and burn. Though to get the right coffee is from the roasting process. Roasting determines the color and variety of flavors of coffee to be consumed. The effect of temperature and time also affects the results of roasting, even when roasting here we monitor the thickness of coffee beans. to produce good roasting. The principle is to give the right amount of time and the right temperature so that coffee will not only have a fragrant aroma but also create the right taste. To solve the problem, in this article we made coffee bean roasters. This coffee bean roasting system is based on Arduino MEGA type 2560. The roasting process uses the mlx90614 sensor and DHT11 sensor to monitor the moisture of coffee beans that will be displayed on the 7-segment. The heating media used is using heat elements instead of stoves. This tool is able to roast as much as 400 grams of coffee. It is expected that the roasting machine of coffee beans will be more optimal